Whole-Genome Sequencing of Bradyrhizobium diazoefficiens 113-2 and Comparative Genomic Analysis Provide Molecular Insights Into Species Specificity and Host Specificity - Li, Rong; Feng, Yong; Chen, Haifeng; Zhang, Chanjuan; Huang, Yi; Chen, Limiao; Hao, Qingnan; Cao, Dong; Yuan, Songli; Zhou, Xinan (Frontiers in Microbiology, 2020)
In the present study, we sequenced the complete genome of Bradyrhizobium diazoefficiens 113-2. The genomic characteristics of six selected rhizobial strains (two fast-growing rhizobia, two medium-slow-growing rhizobia and two slow-growing rhizobia) with four different legume hosts were analyzed by comparative genomic analysis. Genomes of B. diazoefficiens 113-2 and B. diazoefficiens USDA110 were found to share a large synteny blocks and a high ANI value, supporting 113-2 as a strain of B. diazoefficiens. 5455 singletons and 11656 clusters were identified among the six rhizobia genomes, and most of the pair-wise comparisons clusters were shared by the two genomes of strains in the same genus. Similar genus-specific gene numbers in the assigned COG functional terms were present in the two strains of the same genus, while the numbers were decreased with the increase of growth rate in most of the COG terms. KEGG pathway analysis of B. diazoefficiens 113-2 suggested that the rhizobial genes in ABC transporters and Two-Component system were mainly species-specific. Besides, the candidate genes related to secretion system and surface polysaccharides biosynthesis in the genomes of the six strains were explored and compared. 39 nodulation gene families, 12 nif gene families and 10 fix gene families in the genomes of these six strains were identified, and gene classes in most of gene families and the types and total gene numbers of gene families were substantially different among these six genomes. We also performed synteny analyses for above-mentioned nod, nif and fix gene groupings, and selected NodW, NolK, NoeJ, NifB, FixK and FixJ gene families to perform phylogeny analyses. Our results provided valuable molecular insights into species specificity and host specificity. The genetic information responsible for host specificity will play important roles in expanding the host range of rhizobia among legumes, which might provide new clues for the understanding of the genetic determinants of non-legume-rhizobium symbiosis.